Non-Hazardous Waste Management Analysis of Aircraft Operations to Improve Airside Area Aviation Safety in I Gusti Ngurah Rai Airport: Analisis Penanganan Limbah Non-B3 Hasil Pengoperasian Pesawat Udara Dalam Rangka Meningkatkan Keselamatan Penerbangan di Area Sisi Udara Bandara I Gusti Ngurah Rai - Gilbert N. L. Siregar; Ubaedillah; Imam Sonhaji (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The rapid growth of the air transportation sector has significantly increased the production of non-hazardous waste in the airside area of airports. This study aims to analyze the non-hazardous waste management system from aircraft operations at I Gusti Ngurah Rai International Airport to improve aviation safety. This research employs a descriptive qualitative approach, utilizing observation, semi-structured interviews, and field documentation. The findings reveal that non-hazardous waste management remains suboptimal, characterized by the absence of Temporary Storage Sites (TPS), lack of formal Standard Operating Procedures (SOP), and weak inter-unit coordination. These conditions potentially cause waste accumulation in active operational areas, increasing the risk of Foreign Object Debris (FOD) and compromising flight safety. The study recommends the construction of TPS in compliance with safety standards, establishment of SOPs, implementation of digital control systems, and capacity building through continuous training. The implementation of these strategies is expected to create an orderly, clean operational environment that supports aviation safety at I Gusti Ngurah Rai Airport.